The Emerging U.S. Current Account Deficit in the 1980s: A Cointegration Analysis - Husted, Steven (The Review of Economics and Statistics, 1992)
This paper seeks to understand the recent history of U.S. external imbalances by identifying the "long-run tendency" of the U.S. current account balance and investigating its behavior. The procedure that is adopted is to estimate cointegrating regressions between U.S. exports and imports of goods and services. Estimates from cointegrating regressions between several measures of U.S. exports and imports show that up to about the end of 1983 the U.S. current account tended toward zero. Since that time, there has been an apparent structural shift resulting in a long-run tendency for a deficit in excess of $100 billion per year. Copyright 1992 by MIT Press.